APPLICATION OF AUDIT STANDARD NUMBER 300 (REVISION 2021) CONCERNING PLANNING AN AUDIT OF FINANCIAL STATEMENTS AND AUDITORS CONSIDERATION OF AUDIT PROCEDURES - Sry Theresia Angel Vaulina; Ramot P. Simanjuntak (Universitas Kristen Indonesia, 2023)
With regard to arranging an audit of financial statements for audit processes, Auditing Standard Number 300 (Revised 2021) will be examined in this study, as well as the auditor's consideration of the audit procedures used by the auditor at the East Jakarta Public Accountant Office (KAP). This study used quantitative research methods and direct distribution of questionnaires to East Jakarta-based auditors in order to collect data. Purposive sampling with sample criteria was used to choose the sample for this investigation. 1) A minimum of one year of employment 2) being certified as a public accountant (CPA) 3) auditors who were involved in the creation of audit plans 4) auditors who are familiar with Audit Standard 300 (2021 Revision). In this study, 60 auditors who worked in five KAPs in East Jakarta participated as respondents. Data analysis techniques such as descriptive analysis, the traditional assumption test, multiple linear regression analysis, and hypothesis testing were used to evaluate this work. Results of the test and t count t table (4.954 > 1.677) with a significant value of 0.000, less than 0.05, or 5%, for the variable Application of Audit Standards number 300 (Revised 2021). In light of the fact that Ho is rejected and Ha is accepted, it can be said that the variable corresponding to Audit Standard Number 300 (Revised 2021) has a favorable and significant impact on audit operations. And with a significance of 0.000 less than 0.05 or 5%, the value of Fcount Fcount>Ftable (14.598 > 3.155) was also significant. Therefore, it can be said that Ho is rejected and accepted by Ha, indicating that the variables Auditor's Considerations (X2) and Application of audit Standards number 300 (Revised 2021) (X1) together (simultaneously) have a favorable and significant impact on audit operations. Author recommendations: 1) The following researcher broadens the study's subject and eligibility requirements for participants. 2) The next researcher combines the dependent and independent variables. 3) The following researcher includes other study techniques, like interviews. Keywords: audit standard number 300 (revision 2021), auditor's considerations, and audit procedures